2017
DOI: 10.19030/jabr.v33i3.9935
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Linear Relationship Between CEO Compensation Incentives And Corporate Tax Avoidance

Abstract: This study examines the effect of CEO compensation incentives on corporate tax avoidance. Unlike prior literature that assumes a monotonic relation between executive compensation incentives and tax avoidance, we find a non-linear relation between the two. Specifically, we find that CEO compensation incentives exhibit a positive relation with corporate tax avoidance at low levels of compensation incentives, whereas they show a negative relation at high levels of compensation incentives. We further find that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…This result is supported by Hariyanto and Utomo's (2018) research, which reports that executive compensation has a significant proportional impact concerning corporate tax avoidance because compensation with fantastic value will harmonize managers' and shareholders' thinking. Also, Chee et al (2017) stated that CEO tax avoidance strategy on high executive compensation is different from CEO tax avoidance strategy on low executive compensation. It is different from the research conducted by Putra, Andreas, and Nasrizal (2018), which states that there is no effect of executive compensation on corporate earnings management practices because executive compensation is only dominated by fixed compensation such as salaries and allowances.…”
Section: The Effect Of Executive Compensation On Tax Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…This result is supported by Hariyanto and Utomo's (2018) research, which reports that executive compensation has a significant proportional impact concerning corporate tax avoidance because compensation with fantastic value will harmonize managers' and shareholders' thinking. Also, Chee et al (2017) stated that CEO tax avoidance strategy on high executive compensation is different from CEO tax avoidance strategy on low executive compensation. It is different from the research conducted by Putra, Andreas, and Nasrizal (2018), which states that there is no effect of executive compensation on corporate earnings management practices because executive compensation is only dominated by fixed compensation such as salaries and allowances.…”
Section: The Effect Of Executive Compensation On Tax Avoidancementioning
confidence: 99%
“…This statement is reinforced by the results of Hansen, Lopez, and Reitenga (2016), which prove that there is a tax relationship with sufficient compensation. Research by Chee, Choi, and Shin (2017) states that executive compensation and tax avoidance have a positive relationship with low executive compensation but a negative relationship with high levels of executive compensation. Apart from that, Hariyanto and Utomo (2018); Rosidy and Nugroho (2019) state a negative influence between executive compensation and ETR.…”
Section: Introductionmentioning
confidence: 99%
“…However, this research is in line with Uygur (2013) with the result that greater executive compensation can actually encourage accounting fraud. (Chee et al, 2017) also found evidence that greater executive compensation encourages greater fraud in corporate tax avoidance. (Bartenputra, 2016) that compensation does not affect the tendency of accounting fraud.…”
Section: Resultsmentioning
confidence: 92%
“…Uygur (2013) with the result that greater executive compensation can actually encourage accounting fraud. (Chee, Choi, & Shin, 2017) also found evidence that the greater executive compensation encourages the greater fraud in corporate tax avoidance. The existence of compensation contracts given to company executives can also negatively impact the policies taken by company executives.…”
Section: Literature Review Executive Compensationmentioning
confidence: 92%
“…Previous studies have examined the effect of CEO characteristics on the tax aggressiveness level beside the capital structure choice and consequently on the shareholder's wealth beside stock crash risk (Neifar et.al. 2019;Chee et al, 2017;Chen et al, 2019;Huang, 2019;James, 2019). Furthermore, according to (Chancharat et al, 2012), the CEO characteristics have an essential role to mitigate firm risky failure.…”
Section: Introductionmentioning
confidence: 99%